2000
DOI: 10.1006/viro.2000.0358
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Vibrio eltor MAK757 to Classical Biotype: Role of Phage PS166

Abstract: Temperate phage PS166 infection of Vibrio eltor MAK757 resulted in complete changes in all biotype-specific determinants. About 10% of the PS166 lysogens of MAK757 lost their eltor-specific determinants, namely, the ability to produce soluble hemolysin, cell-associated hemagglutinin for chicken erythrocytes, and resistance to polymyxin B, as well as resistance to Mukherjee's group IV phage and sensitivity to eltor phage e4. These lysogens were found to have acquired the properties of classical strains, most si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…With a V. cholerae genomic microarray that displayed more than 93% of the predicted genes of the whole genome sequence of El Tor strain N16961, Dziejman et al (9) showed that only seven genes were absent solely in classical strains but present in other strains, leading them to speculate that classical biotype strains may be derived from a primordial environmental strain that was more El Tor like than previously thought. Mitra et al have previously reported the involvement of bacteriophage PS166 in the acquisition of some classical biotypespecific properties by El Tor strains (22,23). Insertion of lysogenic phage genomes in the bacterial chromosome leading to the activation or inactivation of certain genes or expression of new phage-encoded genes is a natural phenomenon in the origination of genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…With a V. cholerae genomic microarray that displayed more than 93% of the predicted genes of the whole genome sequence of El Tor strain N16961, Dziejman et al (9) showed that only seven genes were absent solely in classical strains but present in other strains, leading them to speculate that classical biotype strains may be derived from a primordial environmental strain that was more El Tor like than previously thought. Mitra et al have previously reported the involvement of bacteriophage PS166 in the acquisition of some classical biotypespecific properties by El Tor strains (22,23). Insertion of lysogenic phage genomes in the bacterial chromosome leading to the activation or inactivation of certain genes or expression of new phage-encoded genes is a natural phenomenon in the origination of genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Mitra et al (15,16) already described phage genome involvement in the acquisition of some classical biotype specific properties by El Tor strains. However, the exact mechanism of In 1961, with the beginning of the seventh pandemic the classical strains were gradually replaced by the El Tor biotype, and in Bangladesh the gradual replacement occurred from 1968.…”
mentioning
confidence: 99%